2009
DOI: 10.1016/j.ijpsycho.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of sensory gating performance in children with and without sensory processing disorders

Abstract: Recent interest in sensory gating in children with and without neuropsychological disorders has resulted in a number of studies and the results regarding the developmental trajectory of sensory gating are inconsistent. We investigated the maturational course of sensory gating in samples of typically developing children and children with sensory processing deficits (SPD) and compared their performance to adults. Besides gating ratios, we also examined the brain responses to conditioning and test click stimuli i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 47 publications
(102 reference statements)
5
56
0
1
Order By: Relevance
“…Our cohort of healthy children also exhibited smaller suppression scores relative to the scores of healthy adults. This result is in agreement with the reported maturational course of P50 suppression characterized by increasing suppression effects and diminished variability with age (Brinkman and Stauder 2007;Freedman et al 1987;Marshall et al 2004;Davies et al 2009). The frontal cortex has been implicated as one of the key brain areas contributing to P50 suppression (Brinkman and Stauder 2007;Grunwald et al 2003;Knight et al 1999;Weisser et al 2001), and it has been speculated that the maturation pattern of the of P50 suppression effect is related to the documented maturation processes of the frontal cortex during childhood and preadolescence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our cohort of healthy children also exhibited smaller suppression scores relative to the scores of healthy adults. This result is in agreement with the reported maturational course of P50 suppression characterized by increasing suppression effects and diminished variability with age (Brinkman and Stauder 2007;Freedman et al 1987;Marshall et al 2004;Davies et al 2009). The frontal cortex has been implicated as one of the key brain areas contributing to P50 suppression (Brinkman and Stauder 2007;Grunwald et al 2003;Knight et al 1999;Weisser et al 2001), and it has been speculated that the maturation pattern of the of P50 suppression effect is related to the documented maturation processes of the frontal cortex during childhood and preadolescence.…”
Section: Discussionsupporting
confidence: 93%
“…The interplay between deficient efferent brainstem activity and enhanced cortical suppression should be further studied to clarify the full nature of auditory aberrations in SM. Future research on the developmental course of P50 suppression, and possibly other auditory cortical potentials such as N1 (Davies et al 2009), in children with SM may shed light on the potential contribution of inhibitory mechanisms to the process of outgrowing SM during adolescence and early adulthood. …”
Section: Discussionmentioning
confidence: 99%
“…Brain activity correctly differentiated children with SPD from normally developing children with 86% precision. These results are evidence that children with SPD have different mechanisms of reception of sensory information to their peers, which may explain the symptoms of the disorder and in this way confirm the value of the SPD diagnosis (Davies, Chang, & Gavin, 2009;Davies & Gavin, 2007).…”
Section: Neurophysiological Indicators Of Sensory Processing Disordersupporting
confidence: 76%
“…P50 suppression was evident in 90% of the children of the SM group and only in 40% of the controls, whereas augmentation was found in 10% and 60%, respectively. Indeed, previous developmental studies in healthy children describe increase in P50 suppression effects and diminished variability with age (Brinkman and Stauder, 2007;Freedman et al, 1987;Marshall et al, 2004;Davies et al, 2009). It has been suggested that the maturational course of P50 suppression follows the maturation pattern of the frontal cortex (Brinkman and Stauder, 2007;Grunwald et al, 2003;Knight et al, 1999;Weisser et al, 2001).…”
Section: Preliminary Findings On Cortical Efferent Adaptation In Smmentioning
confidence: 95%